2014
DOI: 10.1371/journal.pone.0109366
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Resistance to Diverse Classes of NAMPT Inhibitors

Abstract: Inhibiting NAD biosynthesis by blocking the function of nicotinamide phosphoribosyl transferase (NAMPT) is an attractive therapeutic strategy for targeting tumor metabolism. However, the development of drug resistance commonly limits the efficacy of cancer therapeutics. This study identifies mutations in NAMPT that confer resistance to a novel NAMPT inhibitor, GNE-618, in cell culture and in vivo, thus demonstrating that the cytotoxicity of GNE-618 is on target. We determine the crystal structures of six NAMPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…The link between iNAMPT and cancer is well documented (Garten et al , ; Galli et al , ; Burgos, ; Sampath et al , ); indeed, it is essential for restoration of the NAD pool following over activation of PARPs and SIRTs, in cancer cells (Wang et al , ; Chan et al , ). It is therefore not surprising that iNAMPT is overexpressed and overactive in cancer and represents an exciting new therapeutic target (Wang et al , ; Zak et al , ).…”
Section: Circulating Enampt In Cancermentioning
confidence: 99%
“…The link between iNAMPT and cancer is well documented (Garten et al , ; Galli et al , ; Burgos, ; Sampath et al , ); indeed, it is essential for restoration of the NAD pool following over activation of PARPs and SIRTs, in cancer cells (Wang et al , ; Chan et al , ). It is therefore not surprising that iNAMPT is overexpressed and overactive in cancer and represents an exciting new therapeutic target (Wang et al , ; Zak et al , ).…”
Section: Circulating Enampt In Cancermentioning
confidence: 99%
“…Interestingly, NAMPTis of different classes have differing sensitivities to cells overexpressing these mutants. 76 An additional mutation at residue 165 precludes binding of the phosphoribosylated GNE-618 compound to the enzyme at an allosteric site; however, this mutation preferentially affects some compound classes over others. 76 None of these mutations were identified in a screen of more than 200 normal and tumor tissues, suggesting the lack of pre-existing resistance mutations in patient populations before treatment.…”
Section: Resistance Mechanismsmentioning
confidence: 99%
“…NAMPT, a key enzyme in the NAD + biosynthetic pathway, is a molecular target of potent anticancer candidates, including FK866 and other reported NAMPT inhibitors (1-4). However, many studies have previously reported that NAMPT pointmutations render resistance to specific NAMPT inhibitors in several cancer cell types (14)(15)(16). We investigated the resistance mechanisms of NAMPT inhibitor FK866 in human CRC HCT116 cells (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…NAMPT is a potential anticancer drug target, and many drug candidates have been developed that inhibit its enzymatic activity (1,5), including FK866 (also known as APO866 and WK175) (6, 7), CHS-828 (also known as GMX1778) (8)(9)(10)(11), GNE-617 (12), and STF-118804 (13). Acquired resistance to anticancer NAMPT inhibitors appears to be due to alterations in NAMPT itself (14)(15)(16). There have been previous reports that NAMPT point-mutations confer resistance to specific NAMPT inhibitors (14)(15)(16).…”
mentioning
confidence: 99%
See 1 more Smart Citation